EFFICACY OF YOGA ON TRAUMA IN ORPHAN CHILDREN DWELLING IN ORPHANAGE HOMES: An EXPERIMENTAL PRE POST STUDY - Asima kumar*; Vijay Kumar; Sahana Murthy (AYUSHDHARA, 2018)
Orphans and vulnerable children (OVC) are at increased risk for post-traumatic stress disorder (PTSD), depression and anxiety. They are at a substantially greater risk for developmental problems in cognitive, physiological, social, emotional, and behavioural domains. The aim of present study is to diagnosed the presence of trauma and to study the effect of Integrated Approach of Yoga therapy on participants with post trauma stress disorder. Three orphanages were chosen for the study. The children were divided in to two groups experimental (n=21) and control group (n=21). The children were in the age group 7 to 12. CAPS-CA-5 for DSM-5 (Clinician Administered PTSN Scale child/Adolescent version for Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) was administered prior to the intervention. Only children who satisfied the diagnostic criteria were selected. Yoga group underwent three months of Yoga program in a schedule of 90 min per day, five days per week whereas the Control group followed the routine activities Intervention was given by trained Yoga teachers at the Orphanage. The yoga module included Loosening Practices, Breathing practices, Asanas, Surya Namaskaras, Pranayama, Yogic Games, Devotional songs and Bhajans. Practices were given on weekdays and the participants were assessed after three months.